EFEKTIVITAS METODE PROBLEM BASED LEARNING DAN PENDIDIKAN KARAKTER DALAM MATA KULIAH STATISTIKA DASAR - Amalia Fitri (LPPM Universitas Pekalongan, 2012)
The research objective is obtain the effectiveness of learning mathematics with PBL method and learning instrument that oriented character building better than common teaching method applied in the class. The effectiveness of learning is marked: a) the achievement of exhaustiveness indivudually problem solving skill test exceed for KKM and classical completeness exceed 75%, b) motivation and learning process skill has a positive effect on the problem solving skill, c) the average of problem solving skill test experiment class is better than the control class. Based on the result of this research, it can be concluded that learning mathematics with PBL method and learning instrument that oriented character building better than common teaching method applied in the class. Thus, to improve problem solving skill on elementary statistic’s learning and other materials with the same characteristics suggested PBL method with learning instrument that oriented character building.Keywords : Learning, Character, Problem Solving